ADMINISTRASI PERGUDANGAN PADA CV EASTERN DEPO JAKARTA - Widowati, Retno; Septiawan, Teguh Rizky (JAB (Jurnal Akuntansi & Bisnis), 2021)
This research was conducted to find out how the Warehousing Administration Process on CV. Eastern Depo Jakarta, knowing the constraints and alternative solutions in problem solving. Data collection techniques through observation, namely observing directly the object under study. Based on the results of the discussion shows that the roles and tasks carried out in the Warehousing Administration Process at CV. Eastern Depo Jakarta in accordance with the standard roles and authorities given are generally listed in the Job Description. Constraints that occur are limited space, low productivity and data accuracy are the main topics of discussion in this TA. The solution that is done temporarily has not been effective because from several alternatives sometimes it is still disturbed by urgent work that must take precedence. In the development of the administrative system in the company at least it brings progress slowly but to achieve good development, it is very necessary to support from many parties and focus on developing itKeywords: Administration, Warehousing, Process , System